Pelatihan Pengelolaan Website dengan Wordpress di SDN Utan Kayu Utara 01 - Kristiyanto, Yogi; Wardani, Mursida Kusuma; Andriyani, Meli; Rachman, Muhammad Maulana (Jurnal Pengabdian kepada Masyarakat UBJ, 2024)
The existence of a school website is an important means to convey information effectively to students, teachers, parents, and the general public. SDN Utan Kayu Utara 01, located in East Jakarta, has an official website that can be used as a medium for information and communication. This training aims to provide a basic understanding of the importance of websites in education; train participants to manage websites using WordPress, a platform that is easily accessible and user-friendly; support SDN Utan Kayu Utara 01 in creating a digital platform that supports teaching and learning activities and administration. This training is carried out through three main stages, namely preparation, implementation, evaluation and mentoring. The implementation is carried out in one full day (8 hours) consisting of 3 sessions, namely Introduction to Websites and WordPress, Website Management and File Management. Website management training using WordPress at SDN Utan Kayu Utara 01 has produced several significant achievements, both in terms of participant capabilities and infrastructure management. This training has succeeded in improving teachers' technical skills in managing school websites, such as uploading various types of content such as text, images, and videos to beautify and complete the website page. Website management training using WordPress at SDN Utan Kayu Utara 01 has been successfully implemented. From the evaluation, the majority of participants felt that this training was very useful, especially in facing the demands of digitalization of education.